Advances in Decentralized IoT-Enabled Filtration Systems and Their Role in Providing Safe Water to Underserved and Remote Communities - Ayodeji Idowu Taiwo; Lawani Raymond Isi; Michael Okereke; Oludayo Sofoluwe; Gilbert Isaac Tokunbo Olugbemi; Nkese Amos Essien (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Access to clean and safe water remains a critical global challenge, particularly for underserved and remote communities lacking centralized infrastructure. Decentralized IoT-enabled filtration systems offer an innovative solution by combining advanced water treatment technologies with the real-time monitoring capabilities of the Internet of Things (IoT). These systems ensure water quality, optimize resource use, and provide sustainable water access at the point of need. This paper explores the technological advances driving these systems, their impact on water access, and the economic and social benefits they deliver. It also addresses key challenges, including economic barriers, logistical constraints, and cybersecurity concerns, while offering actionable recommendations to enhance adoption, affordability, and long-term sustainability. Decentralized IoT-enabled filtration systems represent a scalable and adaptive approach to addressing the global water crisis, with significant potential to transform water access for vulnerable populations.